Success in Law Studies - Ezeani, Elimma (Edinburgh University Press, 2013)
Success in Law Studies is a must read for students starting to study a course either wholly or partly focused on the law. Elimma Ezeani's book puts every student of the law in a position to maximise their potential by outlining the tried and tested approaches to the various aspects of legal research, writing and study.